(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the most honorable of his creation, the faithful Prophet, and upon his pure familyThe pure ones and his companions, the noble ones, and after:PashtiThe second section of the book explaining the problems of my father (complete)For my father Hamid Ahmed binAl-Kharzanji, who died in the year 348 AH.God made it easy to publish the first part of it.). He wanted many brothersSearching for the best research in Ajmal, I complete the collection of the second part of it and verify it, and this result has been based on our heritageThe glorious Arab Al-Sana’a is from him. I hope that this humble effort will be of benefit to the students of knowledge and scholarsinterested..